2012
DOI: 10.1073/pnas.1206600109
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence showing that no mitotically active female germline progenitors exist in postnatal mouse ovaries

Abstract: It has been generally accepted for more than half a century that, in most mammalian species, oocytes cannot renew themselves in postnatal or adult life, and that the number of oocytes is already fixed in fetal or neonatal ovaries. This assumption, however, has been challenged over the past decade. In this study, we have taken an endogenous genetic approach to this question and generated a multiple fluorescent Rosa26 rbw/+ ;Ddx4-Cre germline reporter mouse model for in vivo and in vitro tracing of the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
206
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 191 publications
(216 citation statements)
references
References 33 publications
(60 reference statements)
7
206
1
2
Order By: Relevance
“…For example, by tracing the proliferation of cultured Ddx4-positive cells in vitro, a recent study from our group reported that no mitotically active GSCs exist in the postnatal mouse ovary (10). More recently, Lei and Spradling provided evidence to support our findings by showing that no active GSCs could be detected in adult mouse ovaries (11).…”
supporting
confidence: 78%
See 1 more Smart Citation
“…For example, by tracing the proliferation of cultured Ddx4-positive cells in vitro, a recent study from our group reported that no mitotically active GSCs exist in the postnatal mouse ovary (10). More recently, Lei and Spradling provided evidence to support our findings by showing that no active GSCs could be detected in adult mouse ovaries (11).…”
supporting
confidence: 78%
“…In contrast to these reports, other recent reports have provided evidence that adult oogenesis and the so-called GSCs do not exist and have questioned the above-mentioned findings (8)(9)(10)(11)(12). For example, by tracing the proliferation of cultured Ddx4-positive cells in vitro, a recent study from our group reported that no mitotically active GSCs exist in the postnatal mouse ovary (10).…”
mentioning
(Expert classified)
“…Finally, a purified population of PGCs could be injected into ovaries to investigate whether de novo folliculogenesis occurs. This last experimental approach has been recently used by Zhang et al (2012) and by us and will be discussed in the next section.…”
Section: Fgscs Could Originate From Undifferentiated Pgcs or A Subpopmentioning
confidence: 99%
“…Thus, retention in small cysts might represent the way to preserve undifferentiated PGCs within the post-natal ovary. Some evidence exists that in the mouse and in some primate species, including humans pre-meiotic proliferating PGCs/oogonia remain in the post-natal ovary during the first period after birth perhaps until puberty (Motta & Makabe 1982, McClellan et al 2003, Johnson et al 2004, Telfer 2004, Byskov et al 2011, Zhang et al 2012. The question of whether any of these proliferating germ cells become follicle-enclosed oocytes remains open.…”
Section: Fgscs Could Originate From Undifferentiated Pgcs or A Subpopmentioning
confidence: 99%
See 1 more Smart Citation